Dynamic information for Polish and English vowels in syllable onsets and offsets - Jekiel, Mateusz (My University, 2014)
According to the simple target model, vowel targets can be described as “a unifying concept among articulatory, acoustic and perceptual characterizations of vowels” (Strange 1989). Moreover, the model states that the first two oral formants (F1/F2) give sufficient information for vowel identification and the problems with vowel perception derive from variations in their production. Although there is a great deal of acoustic variability for a speaker producing a vowel in different consonantal contexts, the relationship between the vowel targets and the produced vowels still remains, as the listeners can recognise the intended vowels despite the variations. A study by Lindblom and Studdert-Kennedy (1967) argues that listeners compensate for the production undershoot by a perceptual overshoot. Further research in the dynamic specification model proved that vowels in consonant-vowel-consonant (CVC) contexts are identified more accurately then in isolation (Verbrugge et al. 1976), syllable onsets and offsets carry useful information for vowel identification (Strange et at. 1983) and a combination of both syllable onsets and offsets provides a “complex dynamic signal that is highly informative” for vowel identification (Jenkins and Strange 1999: 1208). As this paper deals with Polish learners of English, another key study is by Iverson and Evans (2007), showing that L2 learners with a simple vowel system are less successful in identifying English vowels and use different cues than learners with a complex vowel system. The experiment, based on the paper by Jenkins and Strange (1999), was carried out at the School of English at Adam Mickiewicz University in Poznan. A set of Polish and English vowels in CVC contexts was recorded and modified in Praat according to five different conditions: silent-centre (three initial pitch periods, four final pitch periods), one initial pitch period, five initial pitch periods, four final pitch periods and eight final pitch periods, attenuating the remaining vowel components to silence. The participants of the experiment, five students of AMU School of English (proficiency level) and five students from non-linguistic studies (intermediate level), were asked to identify the vowel they heard by marking the key word on an answer sheet that contained the same vowel. The purpose of the experiment was to establish the adequate amount of dynamic information in syllable onsets and offsets needed for correct vowel identification, to compare Polish and English vowel perception and to see to what extent the dynamic specification model describes Polish speakers' vowel perception. The results showed that (1) both groups had difficulties in identifying English vowels, (2) proficiency-level students had better results from their intermediate-level counterparts (80% in silent-centre condition vs. 48%) and (3) both groups had exceptional results in identifying Polish vowels (over 90% in all conditions). Firstly, the difference between a simple L1 (Polish) and a complex L2 (English) vowel system seems to have a bearing on correct vowel identification. Secondly, it seems possible for EFL students to use the dynamic information for English vowels, as the group’s results correlated with the one’s from Jenkins and Strange (1999). Lastly, the results show a difference between Polish and English vowel perception, as the dynamic information in syllable onsets and offsets seems rather futile for the correct identification of Polish vowels.
Keywords: phonetics; acoustic phonetics; English; Polish